Mortality associated to Hydro-Geomorphologic Disasters in the Lisbon Metropolitan area in the last 150 years - Pereira, Susana (2019)
In Portugal, social impacts caused by floods and landslides in the last 150 years were gathered in the DISASTER database. The mortality patterns of the hydro-geomorphological (HG) disasters were recently explored at the national scale, but the analysis was not expanded to more detailed scales. In the present work we explore the mortality caused by HG disasters in the municipalities of the Great Lisbon area. The main objectives of this work are: (i) the spatio-temporal analysis of hydro-geomorphological disasters occurred in the last 150 years on the Great Lisbon area; (ii) the analysis of the frequency and the temporal evolution of fatal floods and landslides; (iii) the analysis of the spatio-temporal distribution of fatalities; (iv) the verification of gender tendencies in mortalities; and (v) the evaluation of individual and societal risk. Individual risk is evaluated computing mortality rates for floods and landslides, which are calculated based on the annual average population and the annual average of fatalities. Societal risk is evaluated by plotting the annual frequency of flood and landslide cases that generated fatalities (F-N curves) for the Great Lisbon area and the whole country. The highest number of flood and landslide cases and related mortality occurred in the period of 1935–1969. After this period, the number of flood and landslide fatalities decreased. The occurrence of flood fatalities has important clusters in Vila Franca de Xira, Odivelas, Oeiras and Lisbon Municipalities, generally associated with small watersheds. The Vila Franca de Xira municipality counts the highest number of fatalities generated by floods, and 84% occurred during a flash flood event in 25-26 November 1967. Fatalities caused by landslides mainly occurred in Oeiras and Lisbon municipalities. Flash floods caused the majority of fatalities associated with floods, while falls and flows were responsible for the highest number of fatalities associated with landslides. Males were found to have the highest frequency of fatalities. In the case of floods, the majority of fatalities were found both outdoors and inside of buildings in urban areas while fatalities inside buildings and inside a train were dominant in landslide cases.